PROMOSI PERPUSTAKAAN MELALUI MEDIA SOSIAL : BEST PRACTICE - Mustofa Mustofa (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2017)
Until now the promotion of libraries still occupy the position of caretaker (minor) in information science education and libraries in various universities in Indonesia. Therefore, do not be surprised if then the production unit called the library can stagnate and out of business. The development of blog-based libraries will expand the potential of the user base, while the use of freeware-databases is sufficient to be the backbone of library automation. Meanwhile, the promotion of libraries through social networks can be one of the library marketing tools today, especially to seize the youth segment. Facebook and Twitter from the library can serve as a media campaign and help in the development of reading interest. Things that can be promoted through Social Media: 1) Promoting library presence 2) Promoting library collections 3) Achieving excellent service to the community 4) Providing education to the community.